Effect of Xanthone Derivatives on Animal Models of Depression - Xu Zhao, MD; Qunying Chen, MD; Yuan Liu, BS; Chao Xia, BS; Jincheng Shi, MD; Maqing Zheng, PhD (Elsevier, 2014)
Background: Extracts of the plant Hypericum perforatum L. have been traditionally used in folk medicine for the treatment of depressive disorders. Xanthone, a component of Hypericum perforatum L., has been shown to be effective in animal models of depression. Objective: We investigated if 2 xanthone derivatives (1101 and 1105) were as effective as venlafaxine, which is a serotonin-norepinephrine reuptake inhibitor and was used as a positive control, in animal models of depression. Methods: A series of derivatives from xanthone were designed and synthesized. After preliminary experiments, 2 xanthone derivatives (1101 and 1105) were considered to be effective in our mouse depression model. To further determine their effects on depression, classical behavioral despair animal models (forced swim and tail suspension tests) were used to assess the efficacies of these derivatives, whereas venlafaxine hydrochloride was used as a positive control. Oral acute toxicity studies were used to determine if the derivatives were toxic in mice. Results: The oral acute toxicity studies of 2 xanthone derivatives (1101 and 1105) did not show any toxic effect until the dose at 1000 mg/kg body weight, and xanthone derivatives 1101 and 1105 resulted in a significant decrease of the immobility period (in seconds) compared with the untreated control group during the forced swim test with rats (dose = 12 mg/kg; P < 0.05) and mice (dose = 25 mg/kg; P < 0.001). At lower doses, derivatives 1101 and 1105 also decreased the immobility period of rats and mice during the forced swim test but significant differences were only found in mice compared with the untreated control group (P < 0.05). No difference was found between the groups treated with xanthone derivatives and the positive control group during the swimming period in both mice (dose = 25 mg/kg) and rats (dose = 12 mg/kg) (P > 0.05). In the tail suspension test, derivatives 1101 and 1105 produced marked effects with regard to the motion of mice (P < 0.01 or 0.001, respectively) and the derivatives were also noted to have some effects on rats at a dose of 12 mg/kg (P < 0.05). Compared with the positive venlafaxine control group, no differences were found between those treated with either derivative 1101 or derivative 1105 and venlafaxine (P > 0.05). Conclusions: Within certain dose ranges, xanthone derivatives 1101 and 1105 have similar effects to venlafaxine hydrochloride in the treatment of depression as suggested by behavioral despair animal models using rats and mice.